The Emerging Role of Ferroptosis in Liver Diseases - Chen, Si; Zhu, Jun-yao; Zang, Xin; Zhai, Yong-zhen (Frontiers in Cell and Developmental Biology, 2021)
Ferroptosis is a newly discovered type of cell death mediated by iron-dependent lipid peroxide. The disturbance of iron metabolism, imbalance of the amino acid antioxidant system, and lipid peroxide accumulation are considered distinct fingerprints of ferroptosis．﻿The dysregulation of ferroptosis has been intensively studied in recent years due to its participation in various diseases, including cancer, kidney injury, and neurodegenerative diseases. Notably, increasing evidence indicates that ferroptosis plays different roles in a wide spectrum of liver diseases. On the one hand, inhibiting ferroptosis may counteract the pathophysiological progression of several liver diseases, such as alcoholic liver injury, nonalcoholic steatosis hepatitis and fibrosis. On the other hand, inducing ferroptosis ﻿may restrict the emergence of secondary resistance to current medicines, such as sorafenib, for hepatocellular carcinoma (HCC) therapy. Here, we summarize the biological characteristics and regulatory signalling pathways of ferroptosis involved in liver disease. The current available medical agents targeting ferroptosis, including inducers or inhibitors applied in liver diseases, are also reviewed. This work aims to provide new insight into the emerging role of pathogenesis and therapeutic approaches for liver diseases.